Clinical and surgical profile of patients with sequelae of pulmonary tuberculosis who underwent thoracic surgery at a national hospital in Lima, Peru, 2017–2022 - Duran Canevaro, Moises Jacinto (2025)
Objective: To describe the clinical and surgical profile of patients with sequelae of pulmonary tuberculosis (TB) who underwent thoracic surgery at Hospital Nacional Dos de Mayo between 2017 and 2022. Materials and methods: A descriptive and retrospective research involving patients with sequelae of pulmonary TB who underwent thoracic surgery. Data were recorded using Excel 365, and descriptive statistical analysis was performed using IBM SPSS Statistics 26. Results: Atotal of 31 medical records were reviewed. The mean age was 43.90 ± 16.185 years, with a male predominance (61.30 %). Most patients came from Lima (54.80 %) and the Peruvian highlands (41.90 %), and 29.00 % had completed secondary education. Harmful habits—alcohol and tobacco use—were reported in 25.80 % (n = 8), and 16.10 % (n = 5) had diabetes mellitus. Regarding TB history, 71.00 % (n = 22) of cases were newly diagnosed drug-susceptible TB (DS-TB), 19.40 % (n = 6) were relapsed DS-TB and 9.70 % (n = 3) had multidrug-resistant (MDR) TB. Bronchiectasis was the most common surgical indication (74.10 %, n = 23), followed by aspergilloma (61.20 %, n = 19) and cavitation (19.30 %, n = 6). Lobectomy was the most frequently performed procedure (90.30 %, n = 28), primarily in the right upper lobe. Postoperative complications included surgical site infection (16.10 %, n = 5), bronchopleural fistula (6.50 %, n = 2) and retained hemothorax (3.20 %, n = 1). Conclusions: The clinical and surgical profile of patients with sequelae of pulmonary TB who underwent thoracic surgery at Hospital Nacional Dos de Mayo is characterized by adult males with completed secondary education, mainly from Lima and the Peruvian highlands. Most cases were newly diagnosed and relapsed DS-TB. Bronchiectasis and aspergilloma were the most common surgical indications, with lobectomy being the most frequent surgical procedure. No postoperative deaths were reported.